TOC removal from laundry wastewater by photoelectrochemical process on Fe2O3 nanostructure - Nguyen, H.M.; Phan, Chi; Sen, Tushar; Hoang, A. (Taylor & Francis Ltd., 2015)
Organic compounds in laundry wastewater were degraded by photoelectrochemical (PEC) and electrochemical (EC) processes on a mesoporous α-Fe2O3 nanostructured film. The applied voltage was between 1 and 3 V. The PEC process exhibited higher TOC removal rate than EC process for all testing conditions. The synthesized α-Fe2O3 electrodes remained stable over 3 h of operating time. Moreover, lumped kinetics was applied to model the TOC removal. The experimental data were successfully described by a binary model, which consists of both complete and partial oxidation. It was found that the applied voltage influenced the kinetics constants. The results can be applied to improve the current application of laundry water recycling at domestic level.